Competitiveness and Potential for Indonesian Coffee Export Market Development - Millenia Aurelia; Yusman Syaukat; A Faroby Falatehan (Budapest International Research and Critics University, 2022)
Coffee is one of the plantation commodities that has an important role in Indonesia's economic activities. As one of the leading commodities in the plantation sub-sector, coffee still faces various challenges in international trade. The high level of competition between exporting countries encourages Indonesia to be able to improve the quality and productivity of coffee in order to compete in the international market, so this study was conducted to analyze the competitiveness and potential of the Indonesian coffee export market. This research was conducted on coffee commodities (HS 090111) using time series (2006 – 2020) and cross section 10 Indonesian coffee export destinations. This research uses RCA, EPD, and X-Model Potential Export. The results of the RCA analysis show that Indonesian coffee has comparative competitiveness in the export market, while the results of the EPD analysis show that Indonesian coffee is competitively competitive in all export markets, except for the Japanese market. Indonesian coffee exports in the Japanese market are in retreat. Further analysis with X-Model concludes that Indonesian coffee has the potential to develop an optimistic export market for the markets of Belgium, Italy, Malaysia, Egypt, and the Russian Federation, potentially to the United States, India, Germany, and United Kingdom markets. The Indonesian government is expected to encourage the development of coffee exports to the markets of Belgium, Italy, Malaysia, Egypt, and the Russian Federation as top priority destinations and the United States, India, Germany, and United Kingdom markets as potential export destination groups.